Mesothelioma incidence and mortality in South Africa from 2003 to 2013 - Muteba, Kasongo Michel (My University, 2018)
Background The incidence of mesothelioma in South Africa was expected to increase until around 2022 because of the high production of asbestos in the 1990s and a latency period of 20 to 40 years. Not enough research has been done to determine the burden of mesothelioma and evaluate the impact of asbestos ban policies in South Africa since 2001. This study investigated the burden of mesothelioma among South African men and women from 2003 to 2013, and compared the trends in mesothelioma by province, using four different data repositories. Methods A review of records from Statistics South Africa (Stats SA), the National Cancer Registry (NCR), the Pathology Automation database of the National Institute for Occupational Health, and the Asbestos and Kgalagadi Relief Trusts (ART/KRT), were used to estimate the annual mesothelioma incidence and mortality by province of South Africa from 2003 to 2013. Age-standardized incidence and mortality rates using direct standardization, and the average annual percentage change were calculated using the mid-year populations of South Africa as reported by Stats SA for each province, using the World Health Organization World standard population. A negative binomial regression analysis was conducted to identify factors associated with mesothelioma deaths. Results The NCR reported 1 242 new cases of mesothelioma from 2003 to 2010. The average incidence rate per annum was 155 cases, with an age-standardized incidence rate of 0.619 cases per 100 000 world population in 2003, which gradually decreased to 0.399 by 2010. The official statistics from Stats SA reported an average of 194 mesothelioma deaths per annum between 2003 and 2013, or 2132 mesothelioma deaths in total. During the same period, 385 and 499 cases were recorded in the PATHAUT and the ART/KRT databases, respectively. The average age at diagnosis was 63 years in the NCR data, while the average age at death varied from 63 to 65 years in the StatSA and PATHAUT data, with a sex ratio of 5:1 in the PATHAUT data, and 3:1 in the other databases. The Northern Cape had the highest number of mesothelioma deaths across the years of study, with the age standardized mortality rates varying from 3 to 7 cases per 100 000 standard population. The average annual percent change was -1.65%, showing a decreasing trend over time. The annual age standardized mortality rates were higher than the age standardized incidence rates, decreasing from 0.63 to 0.57 mesothelioma deaths per 100 000 World standard population from 2003 to 2013. There was overwhelming evidence of associations of age, sex, race, and province of death with mesothelioma deaths (P<0.001). The adjusted mortality rate ratio was 1.3 times higher in males compared to females, 5 times higher in the Northern Cape compared to the Western Cape, 21 times higher in those older than 75 years compared to those younger than 40 years, and 3 times higher in Whites compared to Blacks. Conclusion The patterns of mesothelioma observed in this study suggest a decreasing trend in mesothelioma incidence and mortality in South Africa, contrary to previous predictions anticipating an increasing trend until 2022. It can therefore be assumed that the peak of mesothelioma has occurred earlier than expected. Record linkage of the different data repositories could be used to confirm under-reporting of the mesothelioma official statistics. Key words: age-standardized mortality rates, asbestos related diseases, negative binomial regression, average annual percent change
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology and Biostatistics Johannesburg, February 2018.
Keywords: Mesothelioma; Mortality